Wives with The Double Burden: Measuring Gender Justice in the Division of Joint Property of Suku Anak Dalam (SAD) Batin Sembilan Viewed from The Principle of al-Musāwah - Mustika, Dian; Yaswirman, Yaswirman; Warman, Kurnia; Yasniwati, Yasniwati (Institut Agama Islam Negeri Curup, 2025)
This research aims to analyze gender justice in the customary provisions of the division of joint property towards wives carrying the double burden in the Muslim community of Suku Anak Dalam (SAD) Batin Sembilan, Jambi, based on the principle of al-musāwah. The customary provisions of this community regulate the division formulation of joint property. Both husband and wife get half a share in the event of divorce or death of one of the parties. However, in reality, wives face the double burden today. In addition to being responsible for household affairs, wives are forced to work to earn a living due to their husbands neglecting their obligations. This research uses an empirical juridical approach. Data were collected through in-depth interviews and documentation. The informants in this research were the customary elders and some residents of SAD Batin Sembilan, while additional information was obtained from the Village Head. The data obtained were analyzed from the gender justice perspective using the principle of al-musāwah. The results showed that based on the principle of al-musāwah emphasizing equality and proportionality (tawāzun), the customary provisions on the joint property division for wives carrying the double burden have not fully promoted the values of gender equality and justice in Islam. On that basis, the joint property division should be added to the contribution/role of the husband and wife in producing marital assets. Thus, based on gender justice considerations, wives carrying the double burden are entitled to a more significant share of the joint property than husbands.